(untitled) (Tribhuvan University Journal of Microbiology, 2018)
Antibiotic resistant bacteria and their resistance determinants have been frequently reported in all types of environments especially in water systems. The collection of antibiotic resistant genes and precursors in host bacteria occupying wastewater environment represents wastewater resistome. This resistome is highly potential to resist almost all types of antibiotics exposed to the environment. Since antimicrobial resistance could be transferred from environmental bacteria to clinical or veterinary pathogens and vice versa, wastewaters systems are spawning grounds for global antibiotic resistance, with potentially serious infection consequences for human and animals. Although the sub-lethal dose of antibiotics is key stimulating factor, however, physiological and environmental stress on bacteria due to various factors including non-antibiotic antimicrobials, organic pollutants like PAHs, chlorinated phenols and heavy metals may also drive the enrichment of antibiotic resistance genes in the environment. Although actual key mechanisms for survival of antibiotic resistance bacteria, proliferation and dissemination of such genes in wastewater are still elusive, this mini review briefly describes environmental resistome, possible drivers and dissemination paths of resistance genes in wastewater systems. Considering the hazards, efficient wastewater treatment technologies are needed to be developed for mitigation of antibiotic resistance bacteria and resistance genes.